MODELING RESIDENTIAL PROPERTY CONSUMERS’ CHOICE: EVIDENCE FROM THE PHILIPPINES - Jose Mari M. Lee; Eduardo G. Ong, (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2020)
The study aims to investigate the relationships between the demographic profile and consumers’ choice particularly price, location, safety and security, facilities and amenities, and exclusivity towards purchase intention of residential property in the Philippines. With the Association of Southeast Asian Nations (ASEAN) Economic Community, the Philippines is viewed by various experts to be in good standing to lead in the area’s property growth. Descriptive-Causal was utilized in the study. The respondents were 400 potential residential property buyers from any of the top 10 real estate developers in the Philippines. The researcher used a purposive sampling method. The data collected through a self-constructed survey questionnaire was entered and analyzed using SPSS and AMOS. The findings of the study showed that the demographic characteristics have a direct effect on consumers’ choice factors. It also revealed that consumers’ choice factors have a direct effect on purchase intention. The researcher proposed an emerging model of the causal relationships between the demographic profile and consumers’ choice factors towards purchase intention of residential property in the Philippines.